ORGANIZATIONAL COMMITMENT: A SUSTAINABLE APPROACH AND APPLICATION - Maxwell Nwinye (Journal Park Publishing, 2022)
Organizations are endlessly faced with the demand and supply challenges coming from the changes in the market. In order for the organization to adjust to the forceful competition in the market place and the rapid changes in technology, it requires employees that are internally or affective committed. The three measures of organizational commitment such as affective commitment, normative commitment, and continuance commitment should be managed, to ensure sustainability. The commitment of workers involves their loyalty, emotional attachment, and willingness to contribute to organizational goals. A high level of organizational commitment is associated with improved opportunities for growth, job performance, fairness, reduced turnover, and organizational citizenship behaviors, Organizations should develop inclusive environment that recognizes rewards, fair policies, growth opportunities, and workers efforts.
Keywords: Organizational commitment, Affective commitment, Normative, continuance.